Peran Jenang Dalam Sistem Pemerintahan Suku Anak Dalam (SAD) Di Kecamatan Air Hitam Kabupaten Sarolangun (Studi Kasus: Jenang Sebagai Nara Hubung dan Resolusi Konflik Suku Anak Dalam (SAD)) - Harpinsyah, Harpinsyah; Miranti, Miranti; Azhari, M. Hasyim (Universitas Muara Bungo, 2025)
This research was conducted in several villages within the Air Hitam Subdistrict, selected due to their involvement and proximity to the subject matter. The study aims to gather comprehensive information and a clear depiction of the Jenang, particularly focusing on the role of the Jenang, and to present it in a series of descriptive sentences that can effectively convey the information to the broader public. What makes this research particularly interesting is that the Jenang is not a member of the Suku Anak Dalam (SAD) community but an ordinary person who holds the highest position within the SAD governance system and exercises autocratic power. This research employs a qualitative approach using a descriptive-analytical method. Informants include the Head of Air Hitam Subdistrict, the Jenang, the Temenggung, the Tengganai, village heads, and community leaders. Data were collected from various literatures, documents, and field research through observation and in-depth interviews. The Jenang plays a significant and far-reaching role in the governance system and everyday life of the Suku Anak Dalam. The Jenang holds multiple roles across various aspects of SAD life. In addition to serving as a leader or government authority, the Jenang is also regarded as a foster father to the Orang Rimba. As the holder of governmental power, the Jenang exercises autocratic authority—every member of the Suku Anak Dalam submits to and obeys the Jenang, whose decisions are final. Interestingly, the Jenang is not a descendant of the Suku Anak Dalam, but rather an outsider, often referred to as Orang Terang (non-SAD).